Exploring Teachers’ and Students’ Perceptions of and Attitudes Towards the use of Blogs for English Writing Skills at a Vietnamese University - Mai, Nguyen Thanh; Bao, Dat (VNU Journal of Science: Education Research; Vol 36 No 4, 2020)
The study aimed at finding out: i) the attitudes of both teachers and students at a Vietnamese university as regards the integration of blogs into English writing classes, and ii) their perceived advantages and difficulties in adopting such a way of teaching and learning. Data was collected in two stages: a preliminary questionnaire survey with 110 students and 12 teachers of EFL (English as a Foreign Language) writing, and follow-up interviews with 07 participants, both teachers and students. Findings indicated participants generally held a positive attitude toward the integration of blogs into EFL writing curriculum. Significant benefits in adopting a blogging approach included teachers’ and students’ access to computer and the Internet, their ability to handle blog-related technical issues, and their awareness of the possible benefits of a blog-integrated curriculum. However, the current limited use of blogs for practicing English writing at the institution as well as students’ willingness to post their writings and give feedback on a public page were among the major obstacles. The study was concluded by some important pedagogical implications for the realization of a blog integrated EFL writing curriculum in Vietnam.